Dystopian Alternative History in Jack Thorne’s Harry Potter and the Cursed Child, Nicholas Wright’s His Dark Materials, and Stephen Briggs’ Night Watch in Light of Possible Worlds Theory - ebtahal elshaikh; ghada mohamed; Hagar Saleh (International Journal of Advanced Humanities Research)
Jack Thorne’s Harry Potter and the Cursed Child (2016), Nicholas Wright’s His Dark Materials (2003), and Stephen Briggs’s Night Watch (2004) are three plays which are adapted from the well-known fantasy novels: J.K. Rowling’s Harry Potter Series, Philip Pullman’s His Dark Materials Trilogy and Terry Pratchett’s Night Watch. This paper attempts to provide a reading of these adapted plays in light of Marie-Laure Ryan’s version of Possible Worlds Theory. To do so, the paper analyzes the three plays from Ryan’s point of view by highlighting the concepts of “plurality of worlds,” “alternate (alternative) history,” “moments of divergence,” “grandfather paradox” and dystopian alternative history. It further demonstrates the theory’s major themes like the counterfactual history, changing history, and time-travel themes. The paper discusses how Ryan’s concept of altering the history is powerfully utilized in the three plays; whereas Thorne and Briggs change the supernatural recorded histories of Harry Potter and the Cursed Child and Night Watch, Wright, in His Dark Materials, changes the natural history of the Reformation era in a fantastical mold. The paper concludes that despite the different perspectives of the three addressed works, the results of changing history are dystopian